Catalyzing Henry reactions in chloroaluminate ionic liquids - Kumar, Anil; Pawar, Sanjay S. (Journal of Molecular Catalysis A - Chemical, 2005)
Henry reactions can be accelerated in chloroaluminate room temperature ionic liquids. The choloroaluminates with higher compositions of organic species of the chloroaluminates prove to be more efficient rate promoters than the ones with lower organic species in catalyzing Henry reactions. involving both aliphatic and aromatic carbonyl compounds. The ionic liquids can be recycled five times to offer good yields. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: chloroaluminates; Henry reactions; ionic liquids; Recycling

Rare earth metal triflates promoted diels-alder reactions in ionic liquids - Sarma, Diganta; Kumar, Anil (Applied Catalysis A-General, 2008)
Rare earth metal triflates, when used with ionic liquids can promote Diels-Alder reactions carried out with different dienes and dienophiles suggesting an enhancement in the catalytic power of the triflates in ionic liquids. It is possible to recover and reuse the ionic liquid phase with triflates to give comparable yields and stereoselectivities even after six cycles. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Diels-Alder reactions; ionic liquids; rare earth metal triflates

Dramatic change in viscosities of pure ionic liquids upon addition of molecular solvents - Khupse, Nageshwar D.; Kumar, Anil (Journal of Solution Chemistry, 2009)
Viscosities of binary mixtures of pyridinium based ionic liquids (1-butyl pyridinium tetrafluoroborate, [BP][BF(4)], 1-butyl 3-methyl pyridinium tetrafluoroborate [3-MBP][BF(4)], 1-butyl 4-methyl pyridinium tetrafluoroborate, [4-MBP][BF(4)]), and phosphonium based ionic liquids, (tetrabutyl phosphonium alaninate, [TBP][Ala]; tetrabutyl phosphonium valinate, [TBP][Val]) with the molecular solvents, water, methanol and dichloromethane, have been measured at 298.15 K. A Brookfield ultra-rheometer was employed to measure the reported viscosities. The drop in viscosity in the close vicinity of pure ionic liquid is more prominent in polar solvents like water compared to less polar solvents. The temperature dependence of this observation was also studied for binary mixtures of [4-MBP][BF(4)] with water in range of 298.15-323.15 K. The Vogel-Fulcher-Tamman (VFT) equation was employed to investigate the temperature dependence of the viscosities of pure pyridinium-based ionic liquids in the temperature range from 298.15-323.15 K.
Keywords: ionic liquids; Molecular solvents; VFT equations; viscosity

Ionic liquids: new materials with wide applications - Khupse, Nageshwar D.; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2010)
Ionic liquids have emerged as possible substitutes for volatile organic solvents and have found many applications in a variety of research areas. In this review, an effort has been made to discuss the special properties of ionic liquids that render these unique solvent media useful in chemical transformations, electrochemical applications, extractions, etc.
Keywords: Chemical processes; Electrochemical devices; ionic liquids; Physicochemical properties; Solvent properties; viscosity

Solvent-induced viscosity changes in ionic liquids - a review - Khupse, Nageshwar D.; Kumar, Anil (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2010)
The high viscosity of several ionic liquids is an undesirable property for their applications in a variety of chemical reactions and electrochemical devices. Addition of a solvent in an ionic liquid is known to reduce its high viscosity to a great extent. In this review, an attempt has been made to examine the published data on the reduction in viscosities of many ionic liquids upon the addition of molecular solvents, including water. A tentative description has been provided for the drop in viscosities under these conditions. Analysis of the viscosity data with the help of empirical equations has been summarized. This critical review also outlines the future outlook of the required studies that might be useful to those who are interested in using ionic liquids for a variety of applications.
Keywords: ionic liquids; solvent; viscosity

Temperature dependent viscosity of mixtures of ionic liquids at different compositions - Khupse, Nageshwar D.; Kurolikar, Shabana R.; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2010)
This work presents experimental investigations of viscosities of the mixtures of ionic liquids, viz., [bmim][BF(4)] + [bmim][PF(6)] and [hmim][BF(4)] + [hmim][PF(6)] at different temperatures. The temperature dependence of viscosities of these mixtures has been analysed in the light of Vogel-Fulcher-Tammann (VFT) equation with excellent accuracy. The viscosities of the mixtures have been analysed using a simple mixing rule.
Keywords: ionic liquids; viscosity

High viscosity of ionic liquids causes rate retardation of Diels-Alder reactions - Kumar, Anil; Pawar, Sanjay S. (Science China-Chemistry, 2012)
Second order rate constants, k (2) have been determined for three bi-molecular Diels-Alder reactions to demonstrate that the high viscosity of ionic liquids can be a detrimental property in carrying out Diels-Alder reactions, if ionic liquids are employed as solvent media. It is possible to enhance the reaction rates of the reaction if a co-solvent is mixed in pure ionic liquid used as a solvent.
Keywords: Diels-Alder reactions; ionic liquids; kinetics; viscosity

Probing thermal interactions of ionic liquids with dimethyl sulfoxide - Rai, Gitanjali; Kumar, Anil (Chemphyschem, 2012)
Interactions between ionic liquids and dimethyl sulfoxide (DMSO) are probed by isothermal titration calorimetry. The excess partial molar enthalpies of ionic liquids H-IL(E) in DMSO are discussed in terms of solutesolvent interactions. The specific interaction theory originally developed by Pitzer is used to analyze the apparent molar enthalpy phi(L) of ionic liquids in DMSO with the help of ion-interaction parameters. Furthermore, quantitative information on solvent reorganization and clathrate formation is obtained and interpreted.
Keywords: calorimetry; dimethyl sulfoxide; ionic liquids; solvent effects; thermochemistry

Unusual salting effects in ionic liquid solutions - Nanda, Raju; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2013)
Unusual salting effects of salting-out agents like LiCl and NaCl and salting-in agents like LiClO4 and NaClO4 in ionic liquid solutions are reported. It is observed that the salting behavior in water can be altered in the presence of ionic liquids. It is demonstrated that the salting-in agents in the presence of the ionic liquids with higher alkyl chain can display unusual fall and rise in the viscosity of the systems. On the other hand, no change in the behavior of the salting-out agents is noted in these ionic liquids. A tentative explanation is proposed for the observed viscosity data in these systems.
Keywords: Cationic ring; ionic liquids; Salting effects; viscosity

Experimental signature of microheterogeneity in ionic liquid-H2O systems and their perturbation by adding Li+ salts: a pulsed gradient spin-echo NMR approach - Nanda, Raju; Rajamohanan, P. R.; Kumar, Anil (Chemphyschem, 2015)
Distinct microheterogeneity has been observed in the [OMIM]Br-H2O system, which is interestingly perturbed by the addition of Li+ salts, indicating unusual diffusivity of [OMIM]Br and H2O molecules. However, the diffusional dynamics of water clusters show contrasting salting behavior at higher concentrations of Li+ salts, following the classical salting phenomenon in lower amounts. In contrast, the existing microheterogeneity in the [BMIM]Br-H2O system is weak enough to show any perturbation caused by the Li+ salts on the NMR time scale.
Keywords: ionic liquids; lithium; microheterogeneity; salt effect; viscosity

Interesting viscosity changes in the aqueous urea-ionic liquid system: effect of alkyl chain length attached to the cationic ring of an ionic liquid - Nanda, Raju; Rai, Gitanjali; Kumar, Anil (Journal of Solution Chemistry, 2015)
In the present article, we demonstrate the effect of urea on the structure of the ionic liquids in their aqueous solutions through viscometric methods. We unravel the structure altering effect of urea in its aqueous solutions of ionic liquids possessing higher alkyl chains. The finding is an attempt to discern the anomalous behavior of urea as shown in the past with the help of many techniques. Interestingly, in the aqueous solutions of the imidazolium based ionic liquids having substitution of -C4H9 and -C6H13 groups on the imidazolium ring, urea exhibits kosmotropic behavior. Further increase in the substituted alkyl group such as -C8H17 alters the urea behavior to be chaotropic.
Keywords: Alkyl chain length; ionic liquids; Structure-breaker; Structure-maker; Urea; viscosity

Synergistic effects and correlating polarity parameters in binary mixtures of ionic liquids - Beniwal, Vijay; Kumar, Anil (Chemphyschem, 2015)
Understanding how a chemical reaction proceeds in solution requires precise knowledge of solute-solvent interactions. Certain issues involved in ionic liquid binary mixtures are still not clearly understood, including: 1) the effects of hydrogen-bond-acceptor basicity () of solvents on the synergistic effects found in ionic liquid-alcohol mixtures, 2) the interrelation between the polarity parameters in binary mixtures, and 3) the application of a model for the description of normalised electronic transition energy for all the binary mixtures. Here, a detailed analysis of polarity parameters in both hydrophilic and hydrophobic ionic liquids has been carried out. A three-parameter model developed by Roses et al. [J. Chem. Soc. Perkin Trans. 2 1997, 13411348] was found to be applicable to all the binary mixtures, and synergistic effects are generated as a result of high values of alcohols compared with those of the ionic liquids. A strong correlation was observed in the values and hydrophobicities of pure ionic liquids, suggesting that values can play a role in describing synergism.
Keywords: green chemistry; ionic liquids; liquids; noncovalent interactions; solvent effects

Comparative investigation of the ionicity of aprotic and protic ionic liquids in molecular solvents by using conductometry and NMR spectroscopy - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Chemphyschem, 2016)
Electrical conductivity (sigma), viscosity (), and self-diffusion coefficient (D) measurements of binary mixtures of aprotic and protic imidazolium-based ionic liquids with water, dimethyl sulfoxide, and ethylene glycol were measured from 293.15 to 323.15K. The temperature dependence study reveals typical Arrhenius behavior. The ionicities of aprotic ionic liquids were observed to be higher than those of protic ionic liquids in these solvents. The aprotic ionic liquid, 1-butyl-3-methylimidazolium tetrafluoroborate, [bmIm][BF4], displays 100% ionicity in both water and ethylene glycol. The protic ionic liquids in both water and ethylene glycol are classed as good ionic candidates, whereas in DMSO they are classed as having a poor ionic nature. The solvation dynamics of the ionic species of the ionic liquids are illustrated on the basis of the (HNMR)-H-1 chemical shifts of the ionic liquids. The self-diffusion coefficients D of the cation and anion of [HmIm][CH3COO] in D2O and in [D-6]DMSO are determined by using H-1 nuclei with pulsed field gradient spin-echo NMR spectroscopy.
Keywords: conducting materials; Electrochemistry; electrostatic interactions; Ion pairs; ionic liquids

Spectacular rate enhancement of the diels-alder reaction at the ionic liquid/n-hexane interface - Beniwal, Vijay; Manna, Arpan; Kumar, Anil (Chemphyschem, 2016)
The use of the ionic liquid/n-hexane interface as a new class of reaction medium for the Diels-Alder reaction gives large rate enhancements of the order of 10(6) to 10(8) times and high stereoselectivity, as compared to homogeneous media. The rate enhancement is attributed to the H-bonding abilities and polarities of the ionic liquids, whereas the hydrophobicity of ionic liquids was considered to be the factor in controlling stereoselectivity.
Keywords: Diels-Alder reaction; Interfaces; ionic liquids; kinetics; stereoselectivity